Postoperative Cardiac Ischemic Complications in Lung Cancer Patients - O. A. Bolshedvorskaya; K. V. Protasov; Yu. K. Batoroev; P. S. Ulybin; V. V. Dvornichenko (Acta Biomedica Scientifica, 2019)
Background. Perioperative myocardial ischemia often complicates extracardiac surgery. The problems of its prediction, diagnostics, treatment and prevention are not solved. Frequency, structure and clinical features of cardiac ischemic complications of surgical treatment of lung cancer are not well understood.The aim of the study was to investigate the frequency of postoperative myocardial infarction and myocardial ischemia in the surgical treatment of patients with non-small cell lung cancer.Methods. The frequency (%) of myocardial infarction (MI) with and without ST segment elevation of electrocardiogram, acute myocardial ischemia in a complete sample of cancer patients (n = 2051) who underwent treatment for non-small cell lung cancer for the last 10 years was calculated. By comparing the relative indicators and calculating the Odds Ratio (OR), we studied the relationship between the cardiac ischemic events with age, type of surgery, prevalence and localization of the tumour. The clinical manifestations and pathomorphology of postoperative myocardial infarction were analysed.Results. Cardiac ischemic complications of thoracotomy for lung cancer occurred in 2.73 % (95% CI 1.98–3.48) cases. Myocardial infarction with ST segment elevation was recorded in 1.07 % (95% CI 0.58–1.57) patients, MI without ST segment elevation – in 0.54 % (95% CI 0.17–0.9), myocardial ischemia – in 1.12 % (95% CI 0.62–1.63). An increase in the frequency of ischemic events after pneumonectomy was observed compared with lobectomy (OR 6.5, 95% CI 3.5–12.2) and after right-sided pneumonectomy compared with left-sided one (OR 3.2, 95% CI 1.6–6.3), and also the age over 70. Hospital mortality from MI was 39.3 %. According to autopsies of patients who died of МI, coronary atherothrombosis was detected in 2 of 22 cases.Conclusion. In the surgical treatment of non-small cell lung cancer, cardiac ischemic events develop in 2.73 % of patients. The greatest risk is associated with right-sided pneumonectomy.